CSR, SUSTAINABILITY, GOVERNANCE, AND ACCOUNTABILITY: THEIR POSITION IN THE BODY OF KNOWLEDGE - Fauzi, Hasan (International Journal of Contemporary Accounting, 2025)
In the contemporary business landscape, corporate social responsibility (CSR), sustainability, governance, and accountability are becoming increasingly prominent. This study examines these interrelated domains and delineates prospective avenues for future research. The study explores their significance, emphasizing their roles in fostering ethical conduct, transparency, and enduring sustainability. An analysis of the accountability cycle, comprising responsibility, answerability, and enforceability, reveals its function in promoting sustainable practices. A review of the literature illustrates the evolution of theories, frameworks, and reporting standards. Current sustainability research is characterized by fragmented methodologies and inconsistent reporting practices. This study investigated sustainability reporting, emphasizing the need for standardization and digital technologies. The ongoing transformation of the financial system highlights the significance of ESG factors in investment decisions. Three principal challenges confronting businesses were identified: disruptive technology, conflicting stakeholder interests, and unpredictable futures. The relevance of Elkington Triple Bottom Line (TBL) framework is examined, highlighting its contribution to sustainability. This study elucidates literature gaps and proposes a framework for future studies, advocating interdisciplinary collaboration to enhance the theoretical foundations and practical applications of CSR and sustainability. The study concludes by emphasizing the necessity of adaptability, innovation, and cooperation to navigate business complexities and cultivate a sustainable future.